Decoding Tea and Infusions Labels: Understanding Ingredient Lists - Sousa , Ana; Gomes, Mariana; Ribeiro , Cláudia; Gonçalves , Virgínia; Pádua , Inês; Leal , Sandra (Scientific Letters, 2024)
Background: Concerns linking food and public health extend beyond nutrients to include the use of food additives [1-3]. Certain additives, like artificial sweeteners, were associated with higher risk of non-communicable diseases [3], raising doubts about their widespread use. While NutriScore is a nutritional labelling tool that addresses nutrients [2], it overlooks additive quantity, which may have “cocktail effects” on the consumer [1,3]. Tea and infusions (THI) are perceived as unprocessed foods, free of additives [1]. Our previous study showed that THI are primarily consumed by females, with choices being age-dependent [4]. Nevertheless, there are still gaps in the composition of THI products in the Portuguese market, remaining unclear whether all options are “healthy choices”. Objective: The study aimed to evaluate the content of various commercial THI products, focusing on the types and number of additives listed on their labels. Methods: Information was collected from labels of 294 THI products. With first ingredient, products were categorized: tea or plant infusions (non-flavoured, flavoured), fruits, spices, and soluble products. Additive data were categorized with Codex Alimentarius and analyzed using JASP (version 0.18.43). Results: Herbal infusions comprise 57.8% (34.7% non-flavoured and 23.1% flavoured), 29.9% tea (10.9% non-flavoured and 19.0% flavored), 4.8% soluble, and 3.7% consisted of both fruit and spice infusions. Among THI, 43.9% had one to eight additives, including flavours, sweeteners, acidity regulators, bulking/emulsifier agents, antifoaming agent and colour. Flavours were the most prevalent additive (75.6%), appearing in one to three different flavors. Sweeteners were present in soluble THI, 57.1% having three different types. Other products containing sweeteners were spice infusions (18.2%), tea (5.4%) and herbal infusion (4.4%) both flavoured. Conclusions: The study showed the presence of various additives in many THI products and, some of these additives, if consumed uncontrolled, could pose a health threat, especially for the most vulnerable individuals.